Analysis of the production of intellectual property at the National University of Callao through its patents, utility models and inventions - Vidal-Sanchez, Ricardo; Chavez-Gallegos, Eduardo; Solis-Farfan, Roberto; Ipince-Antunez, Daniel; Gomero-Ostos, Nestor; Narciso-Gomez, Kennedy; Pascual-Panduro, Paolo (LACCEI, 2024)
Emerging economies face problems in the administration and enforcement of intellectual property protection in their countries, especially at the university level. Since patents are an important part of intellectual property rights, their study allows understanding the role of universities in the diffusion of technology in society; however, the characterization and production of patents in Latin American universities, especially in Peru, has been little studied. The objective of this article is to fully characterize the patents granted and applied for taking into account the current context to determine their progress, the lines of technological interest and the collaboration networks at the National University of Callao. The research is descriptive, a tracking of documentary and legal information in the field of intellectual property has been done establishing a contextualized concept to the current situation. The patent statistics provided in the article show that, despite the continuous growth seen from 2018 to the present in the production of patents, a constant orientation on patents should be made to students, graduates and teachers of the National University of Callao to increase their participation. In addition, promote the creation of patents through multidisciplinary research to help them understand in a practical way the procedure to be followed for patenting.